Mastering market analytics : business metrics : practice and application - Kozielski, Robert (Emerald Publishing Limited, 2017)
In Mastering Market Analytics, Robert Kozielski presents various measurement systems and marketing metrics, along with common mistakes made by organizations and managers in the process of measuring business activities, and illustrates how to avoid these mistakes. The new turbulent business environment has resulted in the decrease in effectiveness and efficiency of marketing activities, resulting in 50% of campaigns in social media remaining unnoticed by the public in 2016 alone. Response rates on emailing campaigns have dropped, one dollar invested in TV advertising generates only .32 cents of return, which all leaves the question of whether these activities are still effective in the contemporary world. What does effective marketing actually mean and which areas can be measured while assessing organizational effectiveness? Do sales and marketing benefit only the company or do they also generate value for customers? With over twenty years of experience in world markets, Kozielski takes lessons and case studies from Eastern Europe to delve into 76 indicators, divided into four groups: sales, distribution, marketing communication, and ecommerce and social media, exploring from both the strategic and operational points of view. Linking applicable descriptions of the metrics with systems of measurement for these marketing activities and results, Kozielski's work is of interest to marketing scholars and MBA students.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Marketing -- Statistical methods; Commercial statistics